Studying infrared spectroscopy of lead oxide - نصور فريد (Latakia University Journal -Basic Sciences Series, 2019)
The study of transparent oxides (TCO) is of great scientific importance due to its wide scientific applications . Therefore, our study of some physical properties of the lead oxide compound . The measurement of the infrared spectrum shows nine vibration frequencies (360, 425, 750, 1400, 1460, 1650, 1850, 2400, 3450 )cm-1 , the study showed that the smallest value of the refractive index is n=1.7795 for the frequency of the vibrational threshold ν=750cm-1 , and the smallest optical length L=0.0217cm corresponding to the vibrational threshold frequency 3450cm-1 and the largest optical length L=0.7015cm corresponding to the vibrational threshold frequency ν=750cm-1 , showing the largest values for the refractive index and the attenuation coefficient and optical conductivity respectively are n=9.949 , α=46cm-1 , σopt= 1.2146(Ωcm)-1 corresponding to the vibrational threshold frequency at ν=3450cm-1 .